“Identificación, caracterización e incidencia de enfermedades fungosas causantes de marchitez, en allium fistulosum(cebolla china) en Lamas-San Martín” - Diaz Ramos, Moises (2014)
The objective was to assess the incidence and severity of fungal diseases in the cultivation of china onion (Allium fistu/osum) under the effect of eradication and hydrotherapy. The trial was conducted in the horticultura! field "Pacific Fund" and the Plant Health Laboratory of the University National of San Martfn (UNSM), using the completely randomized blocks design consisting of four treatments and four replications. In the laboratory phase showed higher number of plants per mat for T2 to 25.75, the tallest in the acicular leaf T1 to 28.61 cm, greater number of plants in the T1 and major crop in the treatment T1 with 142 g. Field was a 67.94% of affected discs in the treatment T4, the number of healthy bulbs kills not influenced significantly, also resulted in a higher yield for T1 with 1.7467 kg I ha. lt is concluded that the hydrothermal treatment reduces the incidence of fungal diseases. Key words: Allium fistulosum, eradication, phytotherapy, incidence, severity, fungal diseases.